Strenght Analysis of Axially Symmetric Elements with a Series of Rectangular Notches - Dietrich, L.; Miastkowski, J.; Szczebiot, R. (Engineering Transactions, 1992)
Complete solutions for axially-symmetric tensile rods with rectangular notches of arbitrary spacing are presented. On the basis of the obtained solutions both limit values of a diameter of the rod outside notch and appropriate spacings of a series of notches have been determined. Strength analysis of such elements within entire range of their geometrical parameters has also been made. The obtained results are compared with experimental tests on specimens made of aluminium alloy.